Analisis Penerimaan dan Pemahaman Masyarakat Kampung Naga Terhadap Sertifikasi Halal - Nisrina, Ananda; Marlina, Lina; Nadia Salsabila, Putri (Quranomic: Jurnal Ekonomi dan Bisnis Islam, 2025)
Halal certification is important to guarantee the halalness of products, but public understanding of this is often limited, especially in traditional communities, such as Kampung Naga. This research aims to analyze the acceptance and understanding of the Kampung Naga community towards halal certification. The method used is a qualitative approach with in-depth interviews with traditional stakeholders and several local communities. The research results show that public acceptance of halal certification is driven by religious values, but the majority feel that traditional traditions are enough to guarantee the halalness of products. Understanding of the halal certification process is still limited, especially among older people, while the younger generation is more open to the benefits of such certification. This research concludes that although there is awareness of the importance of halal, socialization and assistance is still needed to increase understanding and facilitate the halal certification process in Kampung Naga. Keywords: Acceptance, Understanding, Halal Certification.